Managerial Ability and Carbon Emission Disclosure: Do CEOs Care About This Matter in Indonesia? - Rian Nur Aulia; Antonius Herusetya (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
ABSTRACT This study examines the relationship between entity managerial capability and carbon emission disclosure of publicly listed companies on the Indonesian Stock Exchange, covering the years 2019–2023. Managerial capability is measured using data envelopment analysis (DEA) at the firm level as a decision-making unit using the Demerjian et al. (2012) model, while carbon emission disclosure uses a score for carbon emission disclosure. A final set of 301 firm-year observations was obtained by using a purposive sampling method and the available carbon emission disclosure data. Data analysis using multiple linear regression found evidence contradicting the study's hypothesis, where CEO managerial capability is negatively related to carbon emission disclosure for publicly listed companies in Indonesia. This study's findings imply that carbon emission disclosure, which is part of the global temperature reduction efforts outlined in the 2015 Paris Agreement and part of the Environment, Social, and Governance (ESG) program promoted by regulators, is still not a priority for publicly listed companies in Indonesia.